2011
DOI: 10.1248/bpb.34.1163
|View full text |Cite
|
Sign up to set email alerts
|

Leukotrienes in Nociceptive Pathway and Neuropathic/Inflammatory Pain

Abstract: The purpose of this review is to summarize the recent studies examining the expression of leukotrienes (LTs) and their receptors in nociceptive pathways, and their crucial roles in pathological pain conditions. LTs belong to a large family of lipid mediators, termed eicosanoids, which are derived from arachidonic acids and released from the cell membrane by phospholipases. LTs are known to be important factors in a variety of local and systemic diseases and allergic/inflammatory diseases. We examined whether L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 59 publications
1
23
0
2
Order By: Relevance
“…Prostaglandins may act as pro-and anti-inflammatory signals and are not known as effectors of neutrophils (54). Although in-depth characterization of eicosanoids in the urinary tract is required to assess their roles in the sensation of pain and the occurrence of fever, our data support the notion that leukotrienes contribute to inflammation and pain signaling upon activation of the immune system in ASB and UTI cases, consistent with a study on neuropathy where leukotrienes were found to activate their nociceptive receptors (55). Our data also suggest that enzymes degrading leukotrienes, especially those facilitating ␤-oxidation (43), are less active; thus, LTB 4 levels are maintained as long as pathogens are present.…”
Section: Discussionsupporting
confidence: 89%
“…Prostaglandins may act as pro-and anti-inflammatory signals and are not known as effectors of neutrophils (54). Although in-depth characterization of eicosanoids in the urinary tract is required to assess their roles in the sensation of pain and the occurrence of fever, our data support the notion that leukotrienes contribute to inflammation and pain signaling upon activation of the immune system in ASB and UTI cases, consistent with a study on neuropathy where leukotrienes were found to activate their nociceptive receptors (55). Our data also suggest that enzymes degrading leukotrienes, especially those facilitating ␤-oxidation (43), are less active; thus, LTB 4 levels are maintained as long as pathogens are present.…”
Section: Discussionsupporting
confidence: 89%
“…Considering the involvement of both COX and LOX pathways in common inflammatory diseases, such as atherosclerosis (13, 14), abdominal aortic aneurysm (3941), asthma (42, 43), arthritis, and inflammatory pain (13, 44, 45), dual inhibitors of both pathways are of interest (46). Concurrent blockade of mPGES-1 with inhibition of various components of the 5-LOX pathway revealed both predicted and unexpected effects on the human plasma lipidome.…”
Section: Discussionmentioning
confidence: 99%
“…As LOX products have been shown to contribute to nociception also at the spinal level (540,731), results obtained employing either systemically administered LOX inhibitors/leukotriene receptor antagonists with possible brain penetration or LOX knockout animals may reflect leukotriene effects exerted not necessarily in the periphery but possibly in the central nervous system. For this reason, several of the above-mentioned studies must be treated with caution when considering the peripheral pronociceptive effects of leukotrienes.…”
Section: Discussionmentioning
confidence: 99%